PENGARUH CURRENT RATIO, DEBT TO ASSET RATIO, TOTAL ASSET TURNOVER DAN INFLASI TERHADAP RETURN ON ASSET - Herman Supardi; H. Suratno H. Suratno; Suyanto Suyanto (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2016)
This study aims to determine how much influence the current ratio, debt to asset ratio, total asset turnover and inflation on return on assets in registered cooperatives in the Department of Cooperatives, Small and Medium Enterprises, Trade and Industry Indramayu district in 2010-2014 so that it can be used a reference to the management in decision making.This study uses the population, namely Employees Cooperative Republic of Indonesia registered KUKM, Industry and Trade of Indramayu district, 2010-2014, as many as 57 KPRI. The sample in this study amounted to 45 samples by purposive sampling method, using secondary data from the Report of the Annual Member Meeting. The tools used are multiple regression analysis. From this study we concluded: Current ratio variable and inflation does not affect the return on assets, the variable debt to asset ratio and total asset turnover variables affect the return on assets, simultaneously current ratio, debt to asset ratio, total asset turnover and inflation effect on return on assets. It can be concluded that the current ratio is too high to be caused by the amount of current assets that are unemployed or bottlenecks receivables.Keywords: Cooperative, Current Ratio, Debt to Asset Ratio, Total Asset Turnover, Return on Assets Inflation